2016
DOI: 10.15171/ijhpm.2016.103
|View full text |Cite
|
Sign up to set email alerts
|

The Frequency of Alcohol Use in Iranian Urban Population: The Results of a National Network Scale Up Survey

Abstract: Background: In Islamic countries alcohol consumption is considered as against religious values. Therefore, estimation of frequency of alcohol consumptions using direct methods is prone to different biases. In this study, we indirectly estimated the frequency of alcohol use in Iran, in network of a representative sample using network scale up (NSU) method. Methods: In a national survey, about 400 participants aged above 18 at each province, around 12 000 in total, were recruited. In a gender-match face to face… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 23 publications
3
36
2
Order By: Relevance
“…2,3 A nation-wide household mental health survey suggested that 5•7% of the adult population had consumed alcohol in the previous year, 3 with a higher prevalence among men, young adults, single adults, urban areas, and some geographical regions. 3,4 Moreover, alcohol poisoning outbreaks due to the consumption of substandard alcoholic drinks are frequent and contribute to alcohol poisoning deaths and hospitalisations across the country. 5 For example, 768 cases of hospitalisation due to methanol poisoning were reported in eight provinces in Iran over the course of 4 weeks in late 2018; among these patients, 170 had dialysis, 16 were blinded, and 96 died.…”
Section: A Public Health Approach To Alcohol Use and Its Related Harmmentioning
confidence: 99%
“…2,3 A nation-wide household mental health survey suggested that 5•7% of the adult population had consumed alcohol in the previous year, 3 with a higher prevalence among men, young adults, single adults, urban areas, and some geographical regions. 3,4 Moreover, alcohol poisoning outbreaks due to the consumption of substandard alcoholic drinks are frequent and contribute to alcohol poisoning deaths and hospitalisations across the country. 5 For example, 768 cases of hospitalisation due to methanol poisoning were reported in eight provinces in Iran over the course of 4 weeks in late 2018; among these patients, 170 had dialysis, 16 were blinded, and 96 died.…”
Section: A Public Health Approach To Alcohol Use and Its Related Harmmentioning
confidence: 99%
“…According to a national survey conducted in Iran (3), men, university students, and people aged 18 to 30 are more likely to consume alcohol (1,3). In addition, according to a study conducted among 5,231 Iranian university students, alcohol consumption was reported as the most common substance used among this group (1).…”
Section: Alcohol Consumption In Iranmentioning
confidence: 99%
“…In addition, according to a study conducted among 5,231 Iranian university students, alcohol consumption was reported as the most common substance used among this group (1). Regional analysis indicated that university students in some provinces including Fars, Isfahan, Kurdistan, Yazd, Tehran, Zanjan, and Golestan were at a higher risk of alcohol consumption (1,3).…”
Section: Alcohol Consumption In Iranmentioning
confidence: 99%
See 2 more Smart Citations